Clinical improvement in canine pulmonary hypertension with Perna canaliculus oil (PCSO-524) add-on therapy: Effects on exercise tolerance and cough - Nattapon Riengvirodkij; Mookmanee Taechikantaphat; Pichayut Ampapol; Theethach Kovorakul; Sapon Intaranat; Nick Costa; Walasinee Sakcamduang (PLoS ONE, 2025)
Pulmonary hypertension (PH) in dogs, characterized by abnormally high blood pressure in the pulmonary arteries, presents a management challenge, and adjunctive therapies for the standard treatment of sildenafil are needed. This study aimed to determine whether the nutraceutical Perna canaliculus oil (PCSO-524), a marine lipid extract with anti-inflammatory properties, provides additional clinical benefits to dogs with PH. In a prospective, randomized, placebo-controlled trial, seventeen client-owned dogs diagnosed with PH were assigned to receive either PCSO-524 or a placebo as an add-on to their sildenafil-based therapy for 70 days. Key outcomes were evaluated using owner-assessed clinical scores for exercise tolerance and coughing, alongside echocardiographic measurements. The PCSO-524 group demonstrated a statistically significant improvement in exercise tolerance scores by day 70 (P = 0.009). This group also showed a greater reduction in coughing scores compared to the placebo group between day 35 and day 70 (P = 0.03). While the tricuspid regurgitation pressure gradient (TRPG), an estimate of pulmonary pressure, decreased significantly over time in all dogs (P = 0.001), no significant difference was found between the groups for this specific measure. These results indicate that PCSO-524 can serve as a beneficial adjunctive therapy for improving important clinical signs, such as exercise tolerance and coughing, in dogs with PH. This suggests it may be a valuable addition to standard management for enhancing quality of life.